Western Labour Radicalism and the One Big Union - Bercuson, David Jay; Western Canadian Studies Conference (1972 : University of Calgary) (The Twenties in Western Canada: Papers of the Western Canadian Studies Conference, March 1972, 1972)
Analyzes the failure of the One Big Union as well as the historical literature.
Keywords: Canada; Western – History – Congresses